Trend Analysis of Rainfall Data in Divisional Meteorological Stations of Bangladesh (Annals of Bangladesh Agriculture, 2020)
Sixty four years, 1952-2016, rainfall data (monthly rainfall and annual total rainfall) were analyzed using non-parametric methods like Mann-Kendall and Sen’s T test to detect the recent trends in rainfall pattern over seven divisions of Bangladesh. Sen’s non-parametric estimator of slope was frequently used to estimate the magnitude of trend, whose statistical significance was assessed by the Mann–Kendall test. Station basis trend analysis was performed for rainfall data. For rainfall of Bangladesh most of the stations, viz. Dhaka, Sylhet, Rangpur, Khulna showed significant upward trend. There were rising rates of rainfall in some months such as April in Rangpur and September in Khulna and a decreasing trend in some other months as in January in Sylhet were obtained by these statistical tests suggested overall significant changes in rainfall trend in these areas. Monthly rainfall and annual total rainfall were found to decrease at the rates of 4.94 mm/year and 16.11 mm/year, respectively, where the downward trend of monthly total rainfall was insignificant but the trend of annual total rainfall was significant with 5% level of significance.Ann. Bangladesh Agric. (2019) 23(1) : 49-61